2001
DOI: 10.1515/bc.2001.096
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Localisation of Cathepsin S, Cathepsin L and MHC Class II-Associated p41 Isoform of Invariant Chain in Human Lymph Node Tissue

Abstract: Antigen presentation by MHC class II molecules requires cysteine proteases (CP) for two convergent proteolytic processes: stepwise degradation of the invariant chain (Ii) and generation of immunogenic peptides. Their activity is controlled by intracellular CP inhibitors, including presumably the p41 isoform of invariant chain (p41 Ii), which is in vitro a potent inhibitor of cathepsin L but not of cathepsin S. In order to evaluate the inhibitory potential of p41 Ii in antigen-presenting cells (APC), these thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Tissue sections (5 m) from formalin-fixed, paraffin-embedded human lymph nodes were prepared [22] and labeled for CyC, MHC II (HLA-DR), CD68, and FDC. Labeling of lymph node tissue and confocal immunofluorescence microscopy was performed as described previously [21,23].…”
Section: Immunohistochemical Analysis Of Lymph Nodesmentioning
confidence: 88%
See 1 more Smart Citation
“…Tissue sections (5 m) from formalin-fixed, paraffin-embedded human lymph nodes were prepared [22] and labeled for CyC, MHC II (HLA-DR), CD68, and FDC. Labeling of lymph node tissue and confocal immunofluorescence microscopy was performed as described previously [21,23].…”
Section: Immunohistochemical Analysis Of Lymph Nodesmentioning
confidence: 88%
“…Cells were fixed with 4% paraformaldehyde in PBS (pH 7.2) for 1 h and permeabilized with 0.1% Triton X-100 for an additional 5 min. Cells were labeled with antibody and visualized by immunofluorescence microscopy using a confocal laser-scanning microscope, Carl Zeiss LSM 510, as described [21], unless stated otherwise. Anti-CyC 1A2 mAb was labeled with Alexa Fluor TM 488 fluorophore, using Zenon TM One Mouse IgG 1 labeling kit, as recommended by the producer (Molecular Probes) prior to colocalization study of CyC with golgin-97 [11] in immature and mature DC.…”
Section: Confocal Immunofluorescence Microscopymentioning
confidence: 99%
“…Monoclonal antibodies (MAbs) (Krka, d.d., Ljubljana, Slovenia) used in ELISA, IHA and Western blots were prepared from mouse hybridoma cell lines (Schweiger et al, 1997;Zavašnik-Bergant et al, 2001). The cell culture supernatants were purified by affinity chromatography on protein A-Sepharose as recommended by the producer (Pharmacia, Uppsala, Sweden).…”
mentioning
confidence: 99%
“…We have previously reported strong colocalization of p41 Ii with cathepsin S in CD68 + sinus-lining macrophages. 19 This is to be expected, since cathepsin S is a key enzyme capable to degrade Ii, releasing MHC II binding site. 15 Therefore, in sinus-lining macrophages p41 Ii represents cathepsin's S substrate.…”
Section: Discussionmentioning
confidence: 96%
“…Monoclonality of prepared mouse anti-Ii antibodies (2C12 mAb and 5F6 mAb) was confirmed by isoelectric focusing as described. 19 Specific antibodies against human cathepsins L, H and S, used in this study, were also prepared and characterized in our laboratory as previously reported: mouse anti-cathepsin S 1E3 mAb 20 mouse anti-cathepsin H 1D10 mAb 18 and sheep anti-cathepsin L polyclonal antibody (pAb). 21 Characterization of anti-invariant chain monoclonal antibodies by ELISA The specificity and cross-reactivity of anti-Ii (2C12 mAb and 5F6 mAb) were compared by antigen-immobilized ELISA using standard protocol at our department.…”
Section: Production and Selection Of Anti-invariant Chain Monoclonal mentioning
confidence: 99%